2015
DOI: 10.1016/j.biomaterials.2015.02.092
|View full text |Cite
|
Sign up to set email alerts
|

Acellular bi-layer silk fibroin scaffolds support functional tissue regeneration in a rat model of onlay esophagoplasty

Abstract: Surgical management of long-gap esophageal defects with autologous gastrointestinal tissues is frequently associated with adverse complications including organ dysmotility, dysphagia, and donor site morbidity. In order to develop alternative graft options, bi-layer silk fibroin (SF) scaffolds were investigated for their potential to support functional tissue regeneration in a rodent model of esophageal repair. Onlay esophagoplasty was performed with SF matrices (N=40) in adult rats for up to 2 m of implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…Sample visualization was performed with an Axioplan-2 microscope (Carl Zeiss MicroImaging, Thornwood, NY) and representative fields were acquired with Axiovision software (version 4.8). Histomorphometric evaluations (n = 3–4 animals per group) were performed on three independent microscopic fields (20× magnification) using published methods ( Algarrahi et al., 2015 ) to quantify urothelial subpopulations in experimental cohorts.…”
Section: Methodsmentioning
confidence: 99%
“…Sample visualization was performed with an Axioplan-2 microscope (Carl Zeiss MicroImaging, Thornwood, NY) and representative fields were acquired with Axiovision software (version 4.8). Histomorphometric evaluations (n = 3–4 animals per group) were performed on three independent microscopic fields (20× magnification) using published methods ( Algarrahi et al., 2015 ) to quantify urothelial subpopulations in experimental cohorts.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past three decades, a number of acellular biodegradable biomaterials have been explored as alternatives to autologous tissue flaps for repair of partial circumferential, full thickness esophageal defects (Tan et al ., 2012). Patch grafts derived from decellularized tissues such as small intestinal submucosa and urinary bladder submucosa have been utilized for esophageal defect consolidation in a variety of preclinical animal models and short-term clinical trials (Badylak et al ., 2000; Lopes et al ., 2006a, 2006b; Urita et al, 2007; Clough et al ., 2011; Nieponice et al ., 2014; Algarrahi et al ., 2015). However, suboptimal regenerative responses and complications such as scaffold leakage have been reported with these matrix designs, therefore raising doubts about their widespread translation into clinical settings (Urita et al, 2007; Nieponice et al ., 2014; Algarrahi et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically viable biomaterial configurations for patch esophagoplasty must possess optimal structural, mechanical and degradative characteristics sufficient to provide for initial defect reinforcement, but allow for gradual scaffold dissipation and subsequent constructive remodeling without eliciting adverse immune reactions. A recent study from our laboratory has shown that bi-layer silk fibroin (BLSF) matrices derived from Bombyx mori silkworm cocoons exhibited such properties in a rat model of onlay esophagoplasty (Algarrahi et al ., 2015). This biodegradable scaffold design displays dual functionality during wound healing by providing a porous foam compartment permissive for host tissue integration while a buttressing film layer prevents leakage of luminal contents (Seth et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These studies describe regeneration of the esophagus in up to 4 weeks with the presence of an epithelial layer and a disorganized or absent muscle layer. However, more recent studies using silk scaffolding [39][40][41], Poly lactic-co-glycolic acid (PLGA) [42,43], and polyurethane (PU) [28] describe smooth muscle and fibroblast regeneration followed by a squamous epithelial lining. The second objective of this study was to evaluate the feasibility of bridging a long intrathoracic esophageal gap with either an autologous EEC seeded or AF-MSC seeded polyurethane (Biostage™) graft in a porcine model of esophageal loss.…”
mentioning
confidence: 99%